Pengembangan Media Lego Untuk Meningkatkan Hasil Belajar Siswa pada Materi Hidrokarbon di Sekolah Menengah Atas - Jekri Supriadi; Raudhatul Fadhilah*; Tuti Kurniati (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
The difficulty of students in learning chemistry subjects is due to the use of media that is not in accordance with the characteristics of students who want fun-based learning. Therefore, it is necessary to develop a Lego hydrocarbon learning media that is suitable for use as a learning medium for hydrocarbon materials. This study aims to produce a feasible and practical Lego hydrocarbon learning media. The feasibility of the Lego hydrocarbon learning media in terms of two criteria, namely (1) validity is determined from the validation results, (2) practicality is determined from student response questionnaires. This type of research is research and development of the ADDIE model. The results showed that the Lego hydrocarbons learning media was suitable for use as learning media with the eligibility criteria measured from the results of the validity of the material aspects and the aspects of the Lego hydrocarbons media of 0.95 and 0.92, respectively, with very valid criteria. The percentage of practicality from the results of student responses in the initial field trial and the main field trial were 90.42% and 95.64%, respectively, with both very practical criteria. Thus, the Lego hydrocarbon learning media is appropriate to be used as a chemistry learning medium